Wunderkammer – The organisation of things and knowledge in an activity-based era: Scientific essay - Bråten, Ingvard (Nordic Journal of Art & Research, 2020)
This essay questions how we organize things and knowledge. The entrance point is the old cabinets of curiosities (Wunderkammers), specified by a book by Samuel Quiccheberg from 1565, together with the use of a cell office today. Quiccheberg’s book is described as the first thesis on how to organize collections. The cell office also contains things within a system. The subversive use of this office is relevant because of the debates around office landscapes and activity-based workplaces. The essay is composed of several smaller texts. Here are no answers to a formulated issue, but the essay is used as a method to raise questions and look for new contexts.